Pulmonic Valve Repair in a Patient with Isolated Pulmonic Valve Endocarditis and Sickle Cell Disease - Timothy Glew; Migdalia Feliciano; Dennis Finkielstein; Susan Hecht; Daryl Hoffman (Case Reports in Cardiology)
A 49-year-old woman with sickle cell disease presented with one month of exertional dyspnea, weakness, and fever and was diagnosed with isolated pulmonic valve endocarditis secondary to methicillin-resistant Staphylococcus bacteremia in the setting of a peripherally inserted central venous catheter. Chest computerized tomography showed multiple bilateral pulmonary nodular opacities consistent with septic emboli. Transthoracic and transesophageal echocardiograms revealed a large echodensity on the pulmonic valve requiring vegetation excision and pulmonic valve repair. In conclusion, isolated pulmonic valve endocarditis is a rare cause of infective endocarditis that warrants a high index of clinical suspicion. Furthermore the management of patients with sickle cell disease and endocarditis requires special consideration.